2008
DOI: 10.1007/s11751-008-0049-5
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed clubfoot correction with soft-tissue release and selective application of Ilizarov technique

Abstract: The Ilizarov technique is an alternative for the treatment of complex foot deformities in children. The authors retrospectively reviewed children with relapsed clubfoot deformity, treated with soft tissue procedures and additional correction with an Ilizarov frame. Twelve consecutive patients (13 feet) with relapsed clubfoot deformity after previous surgical correction were reviewed. Treatment included open releases. An Ilizarov frame was applied as an adjunct in seven patients (mean age of 7.8 years) with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In children, correction is achieved without the need for soft tissue release, tendon lengthening, or osteotomies [21].The Ilizarov protocol consisted of correction of all elements of the deformity, followed by maintenance of the frame in the corrected position for 4 to 10 weeks, to achieve stabilization of the correction [3,16]. Thus, the Ilizarov technique has been considered a time-consuming procedure, with the additional disadvantages of complicated frame arrangement, pin tract infection, and lack of patient and parent compliance [9].…”
Section: Introductionmentioning
confidence: 99%
“…In children, correction is achieved without the need for soft tissue release, tendon lengthening, or osteotomies [21].The Ilizarov protocol consisted of correction of all elements of the deformity, followed by maintenance of the frame in the corrected position for 4 to 10 weeks, to achieve stabilization of the correction [3,16]. Thus, the Ilizarov technique has been considered a time-consuming procedure, with the additional disadvantages of complicated frame arrangement, pin tract infection, and lack of patient and parent compliance [9].…”
Section: Introductionmentioning
confidence: 99%
“…Upto 4-10 years age group of CTEV deformities-we perform soft tissue release surgeries, which may be combined with bony corrective surgeries like cuboid enucleation and cuboidectomy. In soft tissue release surgeries, posteromedial release, tendoachilis lengthening, steindlars with ankle and sub talar capsulotomy, z plasty of medial tendons, tibialis anterior transfer laterally done for recurrent CTEV (7). We observed that avoiding single long incision in camp surgeries prevents sloughing of skin and having incision on medial and posterior side with breech of skin gives good results.…”
Section: Conservative Managementmentioning
confidence: 79%
“…Above the age group 10 years patients, -soft tissue release surgeries (7) with wedge resection of tarsal bone were performed to correct persistent varus deformity. (8) Base of wedge is dorsolateral and incision given distally through cuboid and proximal to distal pole of calcaneum and neck of talus.…”
Section: Conservative Managementmentioning
confidence: 99%
“…These ranged from just using soft-tissue distraction alone to achieve joint realignment (closed 'bloodless' technique) [2,3,[5][6][7][8][9][10][11][20][21][22]24,26] to the use of an adjunctive soft tissue release, foot distraction osteotomies, or both [2,[12][13][14][15][16][17][18][19]23,[27][28][29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%